Public Debt and Economic Growth in Brazil - Afonso, António (2020)
This paper provides new insights on the relationship between public debt and economic growth in Brazil. We used Granger causality tests, in multivariate and bivariate analyses using respectively VEC and ARDL methodologies, and monthly data over the period 1998:1-2019:11. We find that: i) debt-to-GDP and GDP growth rate have a bi-directional Granger causality relationship; ii) debt can improve growth in the short run and becomes harmful in the long run; iii) GDP growth always reduces debt, both in the short and long run; iv) the dynamic between debt and growth in the long run is influenced by the inflation rate, exchange rate and the Emerging Markets Bond Index Plus (Embi+).